Pharmacoeconomic evaluation of ipragliflozin in combination with metformin in comparison with other regimens of therapy for type 2 diabetes mellitus - A. S. Kolbin; A. A. Kurylev; Yu. E. Balykina; M. A. Proskurin (Izdatelstvo OKI, 2021)
Ipragliflozin is a selective sodium-glucose cotransporter 2 (SGLT2) inhibitor that reduce plasma glucose concentrations by inhibiting glucose reabsorption by the kidney through inhibiting SGLT2 sodium-glucose cotransporter and induce glycosuria. SGLT2 inhibitors are a new class of glucose lowering drugs most recently approved for treatment of type 2 diabetes mellitus (T2DM). Unlike other antidiabetic agents, SGLT2 inhibitors improve glycemic control (by HbA1c) and provide multiple additional benefits, including decreased body weight, blood pressure, and other multiple pleiotropic effects. The completed clinical trials and real world data have provided evidence that including of SGLT2 inhibitors in the treatment of T2DM has benefits of reduction of cardiovascular and renal outcomes. Goal. The aim of the study was to conduct a clinical and economic examination of ipragliflozin in comparison with other regimens of glucose-lowering therapy with other SGLT2 inhibitors. Methods. In carrying out the pharmacoeconomic analysis itself, a cost-effectiveness analysis (CEA) was applied with the calculation of the corresponding cost-effectiveness ratio (CER), incremental cost-effectiveness ratio (ICER) according to the formula, as well as an a «budget impact analysis». Multiple one-way sensitivity analysis, check the robustness of the results of the main scenario results to changes in key parameters such as the cost of drugs and complications of diabetes. The time horizon for analyzing the dynamics of economic consequences when using ipragliflozin as a glucose-lowering therapy for T2DM was 5 years. Results. The weighted average cost per patient per year when using the ipragliflozin treatment strategy is 31,182 rubles. The costs of the empagliflozin strategy are 61,291 rubles per patient. In the case of using dapagliflozin, the weighted average costs are 30,032 rubles per patient per year, the total direct medical costs for the current drug therapy option, calculated on the initial number of target practice in 72,143 patients with type 2 diabetes, amounted to 3,068,642,442 rubles. Analysis of the trend of changes in weighted average costs showed that the broader use of ipragliflozin for the treatment of T2DM in the target population leads to reducing in diabetes related direct medical costs by 6.7 %, while the total economic effect of ipragliflozin introduction over five years will be 501,539,327 rubles. Conclusions. Use of ipragliflozin + metformin in T2DM treatment is a cost-effective strategy compared to empagliflozin + metformin. The combination of ipragliflozin with metformin versus dapagliflozin + metformin is economically feasible in terms of cost-effectiveness.